Biomechanical Assessment of Locked Plating for the Fixation of Patella Fractures. Issue 9 (September 2015) - Wurm, Simone; Augat, Peter; Bühren, Volker
Abstract : Objective: To analyze the mechanical stability of locked plating in comparison with tension-band wiring for the fixation of fractures of the patella. Methods: Biomechanical tests were performed on artificial foam patella specimens comparing an angular stable plate and monocortical screws with tension-band wiring. Tests were performed under combined tension and bending until failure simulating physiological loading of the tibia during walking. Results: Tension-band wiring failed at 66% of the failure load of plating (1052 N, P = 0.002) and had 5 times larger fracture gap displacements ( P = 0.002). Conclusions: Based on the biomechanical advantages, locked plating of the patella may constitute a reasonable alternative in the treatment of patella fractures.